Study to Establish the Relationship between Omeprazole (PPI) and Acute Interstitial Nephritis (AIN) - Bite Bapurao; Swanand Pathak; Ranjit Sidram Ambad (Journal of Pharmacy and Bioallied Sciences)
Introduction: Proton pump inhibitors (PPIs) are the most commonly used drug worldwide. PPIs are benzimidazole derivatives and are basic in nature; therefore, they are dispensed in enteric-coated tablets or capsules to avoid degradation from gastric acid. Aim: Study to establish the relationship between omeprazole (PPI) and acute interstitial nephritis (AIN). Objective: To find the effect of PPI alone, PPI with diclofenac, PPI with ofloxacin on renal function tests. Methods: In the present study, we are analyzing PPI (omeprazole) as a main group. The group is again divided into three subgroups containing six rats in each. The relation between PPI and AIN is observed by the administration of PPI alone. To find this relation, we combine the PPI with nonsteroidal anti-inflammatory drug (NSAID) diclofenac and the antimicrobial agent ofloxacin. Results: Omeprazole 20 mg/kg/day alone showed a statistically significant difference in serum creatinine and blood urea values. Omeprazole 20 mg/kg/day and ofloxacin 60 mg/kg/day did not show a statistically significant difference in serum creatinine and blood urea values. Omeprazole 20 mg/kg/day and diclofenac showed statistically significant difference in serum creatinine and blood urea values. Conclusion: With longer administration of PPIs, it did produce derangement of renal function tests (RFTs), and with concurrent administration of drugs like ofloxacin and diclofenac, it hastened the process of renal damage as indicated by deranged RFTs.